Current status and perspective of persimmon research in China - Yuhan Dong; Xinyi Yu; Xialin Ye; Zhihong Gao; Sanhong Wang; Shenchun Qu (Technology in Horticulture)
The persimmon, belonging to the genus Diospyros, is one of the most common fruits with high edible and economic value. China has the largest cultivated area and annual production of persimmons in the world. Pollination-constant nonastringent (PCNA) persimmon, which has great advantages of natural deastringency and direct edibility, has been a key target for industry development and variety selection worldwide. However, there are still many challenges in the development of persimmons in China; for example, the ineffective cost of artificial deastringency treatment of persimmons, laborious breeding of fine varieties of PCNA persimmon, and severe symptoms of delayed graft-incompatibility. This review summarizes the current status and development of persimmons in China. The current progress on the removal of astringency in persimmons, screening of rootstocks with wide compatibility, and the breeding process of PCNA persimmon is highlighted. This review will help promote the breeding of excellent persimmon varieties and the sustainable development of the persimmon industry in China.